Caramel colour and process by-products in foods and beverages: Part I – Development of a UPLC-MS/MS isotope dilution method for determination of 2-acetyl-4-(1, 2, 3, 4-tetrahydroxybutyl)imidazole (THI), 4-methylimidazole (4-MEI) and 2-methylimidazol (2-MEI). (30th July 2018) - Jacobs, G.; Voorspoels, S.; Vloemans, P.; Fierens, T.; Van Holderbeke, M.; Cornelis, C.; Sioen, I.; De Maeyer, M.; Vinkx, C.; Vanermen, G.
Highlights: Development of a new quantification method for caramel colour process contaminants. Detailed validation and analysis of different types of food samples. Analysis of more than 500 food samples. Abstract: Caramel colours are used by the food industry in a wide range of foods and beverages. During their manufacturing, low molecular weight compounds such as 4-methylimidazole (4-MEI), the structural isomer of 4-MEI, 2-methylimidazole (2-MEI) and 2-acetyl-4-tetrahydroxy-butylimidazole (THI) are generated. The presence of these inevitable by-products of caramel manufacturing can be hazardous to human health. This publication describes an isotope dilution Ultra-High-performance Liquid Chromatography tandem mass spectrometric method (UHPLC-MS/MS) that was developed and validated for the simultaneous quantification of these impurities in both beverages/liquids and foods. A limit of quantification of 5 μg/kg was obtained for 4-MEI and THI. The expanded measurement uncertainty (U; k  = 2) for these compounds was below 51% in beverages/liquids and below 56% in foods. As higher measurement uncertainties were obtained for 2-MEI, the developed analytical procedure can only be used in a semi-quantitative way for this compound.